Criminal Liability Arising from Medical Malpractice on Patients: A Review from the Perspective of Positive Law And Islamic Law - Rini Apriyani; Erna Susanti; Poppilea Erwinta; Kalen Sanata; Muh. Sakur (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
The suspicion in cases of medical malpractice in is only slightly raised, meanwhile, there are actions by the health profession by doctors as medical personnel which have the potential to be a malpractice that can be reported by the public, but are not resolved legally because the community only has limited knowledge of science medical and because there is no form of specific legal regulations governing malpractice in Indonesia so that the occurrence of these malpractices can cause legal problems. This study aims to determine criminal liability for medical malpractice acts committed by doctors to patients in anticipating and dealing with medical malpractice problems in criminal cases. The research method used in this study is doctrinal, where the author collects material from the literature, both hardcopy and softcopy, which is related to the title of this research by using an analysis of the research object. Criminal malpractice occurs when a patient dies or is disabled and/or seriously injured as a result of actions taken by health workers who are careless or less careful in making efforts to treat patients who die or are disabled and are criminally liable as a result of medical malpractice acts committed. doctors on patients can be accounted for under Article 359 and Article 360 of the Criminal Code. In this case the health law is considered insufficient and does not clearly regulate the crime of medical malpractice. So it is necessary to regulate the crime of medical malpractice by giving birth to a new health law, namely by explicitly regulating criminal liability for medical malpractice acts by doctors against patients in Indonesia